MINIMUM INHIBITORY CONCENTRATION OF PURPLE LEAF EXTRACT (GRAPTOPHYLLUM PICTUM L. GRIFF) AGAINST LACTOBACILLUS ACIDOPHILUS ATCC 4356 - Indriyani Chusnadia, Shafira; Kurniawati, Atik; Setyaningsih, Sari; Wulandari, Erawati; Astuti, Pudji (Faculty of Vocational Studies, Universitas Airlangga, 2023)
Background: Dental caries is an oral cavity disease that affects most Indonesians. Lactobacillus acidophilus (L. acidophilus) is one of the bacteria that causes dental caries. Control of bacteria in the form of antibacterial agents is needed to suppress the growth of L. acidophilus. Purple leaves (Graptophyllum pictum L. Griff) are a medicinal plant with antibacterial compounds, namely flavonoids, alkaloids, saponins, and tannins. Purpose: Determine the Minimum Inhibitory Concentration (MIC) of purple leaves extract on the growth of L. acidophilus. Method: The sample consisted of seven groups, including positive control (chlorhexidine 0.2%), negative control (BHI-B), and purple leaves extract with concentrations of 25%, 12.5%, 6.25%, 3.12%, and 1.56%. The antibacterial activity of purple leaves extract was carried out quantitatively using a spectrophotometer with a wavelength of 600 nm. After that, it was incubated at 37°C for 48 hours, followed by absorbance measurement. The absorbance results were then analyzed using the Paired T-Test (before and after incubation). Result: Purple leaves extract concentrations of 6.25%, 12.5%, and 25% had an inhibitory effect on L. acidophillus. Conclusion: Minimum Inhibitory Concentration (MIC) of purple leaves extract on the growth of L. acidophilus was 6.25%